Impacts of temperature and surface finish upon steam oxidation of austenitic steel TP347HFG - Bouvet, Justin; Sumner, Joy; Nigel, Simms (Elsevier, 2017)
The effects of the steam oxidation process on an austenitic steel (TP347HFG) exposed under isothermal conditions between 600 and 800 °C for up to 2500 h have been investigated. Samples with both as-received and ground surfaces have been exposed and the impact of surface finish on the oxidation process analysed using scanning electron microscopy with energy dispersive X-ray analysis. Exfoliated oxide flakes have also been examined to characterise their microstructures on fractured sections as well as external and spalled surfaces. Microscopic analyses demonstrated that ground surfaces possess better steam oxidation resistance than as-received surfaces due to their ability to form a more protective chromium-rich layer. The formation of regions of thicker multi-layered oxides was noted on both types of surface finish, covering large areas on as-received surfaces and only nodules on ground surfaces (spreading with increasing exposure temperature and time).
Keywords: Steam oxidation; exfoliation; surface finish; oxide morphology; austenitic steel